Skin sensitization induced Langerhans' cell mobilization: variable requirements for tumour necrosis factor‐α. Issue 1 (January 2015) - Eaton, Laura H.; Roberts, Ruth A.; Kimber, Ian; Dearman, Rebecca J.; Metryka, Aleksandra
Summary Upon antigen/allergen recognition, epidermal Langerhans' cells (LC) are mobilized and migrate to the local lymph node where they play a major role in initiating or regulating immune responses. It had been proposed that all chemical allergens induce LC migration via common cytokine signals delivered by TNF‐α and IL‐1β. Here the dependence of LC migration on TNF‐α following treatment of mice with various chemical allergens has been investigated. It was found that under standard conditions the allergens oxazolone, paraphenylene diamine, and trimellitic anhydride, in addition to the skin irritant sodium lauryl sulfate, were unable to trigger LC mobilization in the absence of TNF‐α signalling. In contrast, two members of the dinitrohalobenezene family (2, 4‐dinitrochlorobenzene [DNCB] and 2, 4‐dinitrofluorobenzene [DNFB]) promoted LC migration independently of TNF‐R2 (the sole TNF‐α receptor expressed by LC) and TNF‐α although the presence of IL‐1β was still required. However, increasing doses of oxazolone overcame the requirement of TNF‐α for LC mobilization, whereas lower doses of DNCB were still able to induce LC migration in a TNF‐α‐independent manner. These novel findings demonstrate unexpected heterogeneity among chemical allergens and furthermore that LC can be induced to migrate from the epidermis via different mechanisms that are either dependent or independent of TNF‐α. Although the exact mechanisms with regard to the signals that activate LC have yet to be elucidated, these differences may translate into functional speciation that will likely impact on the extent and quality of allergic sensitization.